2021
DOI: 10.1093/molbev/msab184
|View full text |Cite
|
Sign up to set email alerts
|

Tunicates Illuminate the Enigmatic Evolution of Chordate Metallothioneins by Gene Gains and Losses, Independent Modular Expansions, and Functional Convergences

Abstract: To investigate novel patterns and processes of protein evolution, we have focused in the metallothioneins (MTs), a singular group of metal-binding, cysteine-rich proteins that, due to their high degree of sequence diversity, still represents a black hole in Evolutionary Biology. We have identified and analyzed more than 160 new MTs in non-vertebrate chordates (especially in 37 species of ascidians, 4 thaliaceans and 3 appendicularians) showing that prototypic tunicate MTs are mono-modular proteins with a perva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 73 publications
3
16
0
Order By: Relevance
“…Notice that the 12C domain of OdiMT1 is, indeed, an 11C domain due to a Cys to Ser substitution in the carboxyl terminal region in comparison with prototypical 12C domain (thus, we named this domain as 11C/12C; Figure 1). Our results showed that this 11C/12C domain was able to yield almost unique Zn 4and Cd 4 -protein species (Figure 2), in a similar way that other domains with 11 or 12 Cys: the 11C mammal and echinoderm α domains (Stillman et al, 1987;Tomas et al, 2013), the 12C mollusk α domains (Digilio et al, 2009), the insect 12C MTs (Egli et al, 2006) and the ascidian and thaliacean 12C MTs (Calatayud et al, 2021a). These results revealed a significant structural and functional autonomy of O. dioica 11C/12C domain, which was able to form stable metal-protein clusters with Zn(II) and Cd(II).…”
Section: Metal-binding Capabilities Of 12c and T-12c Domainssupporting
confidence: 66%
See 4 more Smart Citations
“…Notice that the 12C domain of OdiMT1 is, indeed, an 11C domain due to a Cys to Ser substitution in the carboxyl terminal region in comparison with prototypical 12C domain (thus, we named this domain as 11C/12C; Figure 1). Our results showed that this 11C/12C domain was able to yield almost unique Zn 4and Cd 4 -protein species (Figure 2), in a similar way that other domains with 11 or 12 Cys: the 11C mammal and echinoderm α domains (Stillman et al, 1987;Tomas et al, 2013), the 12C mollusk α domains (Digilio et al, 2009), the insect 12C MTs (Egli et al, 2006) and the ascidian and thaliacean 12C MTs (Calatayud et al, 2021a). These results revealed a significant structural and functional autonomy of O. dioica 11C/12C domain, which was able to form stable metal-protein clusters with Zn(II) and Cd(II).…”
Section: Metal-binding Capabilities Of 12c and T-12c Domainssupporting
confidence: 66%
“…The arrangement of Cys motifs in O. dioica domains diverges from that found in the MTs of other tunicates belonging to the ascidian and thaliacean classes, but it is similar to that of other appendicularian species of the same genus, O. albicans and O. vanhoeffeni (Calatayud et al, 2021a). Comparison of the appendicularian MTs show that the original Oikopleura MT domain had twelve cysteines (12C), and that this domain corresponds to previously described C7 + C5 subunits (Calatayud et al, 2018(Calatayud et al, , 2021a. OdiMT1 would have therefore two 12C domains, but its amino-terminal domain was "trimmed" to become a t-12C domain that lacks the C5 subunit.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations